An intra-vehicular wireless multimedia sensor network for smartphone-based low-cost advanced driver-assistance systems - Myburgh, Hermanus Carel (University of Pretoria, 2022)
Dissertation (MEng (Computer Engineering))--University of Pretoria, 2021.